In vitro study of Streptococcus mutans adhesion on composite resin coated with three surface sealants - Da Hye Kim; Tae-Yub Kwon (Korean Academy of Conservative Dentistry, 2017)
Objectives Although the coating of surface sealants to dental composite resin may potentially reduce bacterial adhesion, there seems to be little information regarding this issue. This preliminary in vitro study investigated the adhesion of Streptococcus mutans (S. mutans) on the dental composite resins coated with three commercial surface sealants. Materials and Methods Composite resin (Filtek Z250) discs (8 mm in diameter, 1 mm in thickness) were fabricated in a mold covered with a Mylar strip (control). In group PoGo, the surfaces were polished with PoGo. In groups PS, OG, and FP, the surfaces polished with PoGo were coated with the corresponding surface sealants (PermaSeal, PS; OptiGuard, OG; Fortify Plus, FP). The surfaces of the materials and S. mutans cells were characterized by various methods. S. mutans adhesion to the surfaces was quantitatively evaluated using flow cytometry (n = 9). Results Group OG achieved the lowest water contact angle among all groups tested (p < 0.001). The cell surface of S. mutans tested showed hydrophobic characteristics. Group PoGo exhibited the greatest bacterial adhesion among all groups tested (p < 0.001). The sealant-coated groups showed statistically similar (groups PS and FP, p > 0.05) or significantly lower (group OG, p < 0.001) bacterial adhesion when compared with the control group. Conclusions The application of the surface sealants significantly reduced S. mutans adhesion to the composite resin polished with the PoGo.